Users’ Perceptions of Mobile Health Apps: Usability, Communication Enhancement, and Healthcare Service Improvement - Sulayao, Jonathan Rey B.; Nurdiana, Astri; Hartiningrum, Chanty Yunie (International Journal of Nursing Information, 2025)
The digital transformation in healthcare has driven the emergence of mHealth applications as strategic innovations that bridge the gap between the limitations of conventional service methods and the demands of modern healthcare delivery. However, the effectiveness of mHealth applications largely depends on how users perceive their usability, their role in enhancing communication, and their contribution to improving healthcare services. This study aims to analyze user perceptions of mHealth applications with a focus on three key dimensions: usability, communication enhancement, and healthcare service improvement. A quantitative approach with a cross-sectional survey design was employed, involving 200 participants from Indonesia and the Philippines selected through purposive sampling. Data were collected via an online questionnaire consisting of 15 items and analyzed using multiple linear regression. The findings reveal that, as perceived by mHealth users, usability exerts a significant effect on communication, and communication acts as a strong predictor of healthcare service improvement. Furthermore, increased usability is consistently predicted to enhance communication effectiveness and healthcare quality, whereas reduced usability may potentially diminish both. In conclusion, as perceived by users, mHealth applications have demonstrated clear advantages over conventional service methods in terms of efficiency, accessibility, and continuity of care. This study contributes by integrating usability, communication, and healthcare service improvement into digital health technology adoption literature, while also offering practical guidance for developers and policymakers in creating more efficient, user-friendly, and sustainable healthcare systems based on user perceptions.